Colombia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2009)
This Selected Issues paper uses contingent claims analysis (CCA) to assess risks to the Colombian banking sector. The CCA approach is based on the estimation of the default probability by an entity on its obligations, and is widely used by rating agencies to assess creditworthiness in the corporate sector. The paper also estimates the effects of changes in selected macroeconomic and financial variables on default probabilities for a sample of Colombian banks. The sample includes five banks for which market-based default probabilities are available.